Coupling geochemical tracers and pesticides to determine recharge origins of a shallow alluvial aquifer: Case study of the Vistrenque hydrogeosystem (SE France). (May 2015) - Sassine, Lara; Khaska, Mahmoud; Ressouche, Sophie; Simler, Roland; Lancelot, Joël; Verdoux, Patrick; Le Gal La Salle, Corinne
Highlights: Sr isotopes are used to highlight the karst water lateral input as well as the direct recharge in the alluvial aquifer. The imported water and stream water contributions are evidenced locally by O and H isotopes and chemical elements. Long term anthropogenic activities are reflected in the evolved geochemical composition of groundwater. The multi-tracer approach is supported by principal component analysis (PCA). Abstract: The objective of this study is to identify the origin of groundwater in a shallow alluvial aquifer, using a multi-tracer approach including δ 18 O, δ 2 H, major elements and 87 Sr/ 86 Sr. In addition, triazines are used as a tracer of water draining agricultural areas. Four potential recharge sources are evidenced in the alluvial groundwater: rainfall, karst water from adjacent aquifer, imported Rhône river water and local stream water. Strontium isotopes are used to highlight the adjacent karst water input (Sr = 6.4–17.6 μmol L −1 ; 87 Sr/ 86 Sr = 0.7076–0.7078) showing a contrasting signature with the pristine alluvial groundwater (Sr = 3.4 μmol L −1 ; 87 Sr/ 86 Sr = 0.7088–0.7092). Lateral karst recharge is observed, with high proportions reaching 100%, all along the North Western border of the aquifer. This lateral recharge implies a dilution in triazines content of the Vistrenque groundwater as the karst area is not used for agriculture. Oxygen-18 and deuterium signatures of local rainwater (δ 2 H = −43.5‰) and imported Rhône River water (δ 2 H = −72.5‰) differ significantly which allows to quantify the influence of imported water on the alluvial groundwater. Such influence is observed only locally in this study. Contribution of local stream water, influenced by wastewater treatment plant effluents, is also locally detected in the alluvial aquifer, using Cl, K, and Na contents. High triazines, NO3, and Cl concentrations underline the vulnerability of this shallow alluvial aquifer to surface contaminations. Finally, the results of this environmental multi-tracer approach are statistically supported by principal component analyses.